Asymmetric volatility spillover between oil market, gold market and Malaysian stock market - Choo, Then Leng; Lim, Jing Yi; Loh, Kean Woh; Sam, Jia Hao; Cheong, Shanny (2020)
This paper examines the asymmetric relationship between oil market volatility, gold market volatility and Malaysian stock market volatility. Monthly data of KLCI, OVX and GVZ which span over the period from January 2009 to December 2018 was obtained from Bloomberg Terminal. Most of the previous studies investigated the linear relationship between oil prices, gold prices and stock market prices. Oil market volatility, gold market volatility and stock market volatility are less investigated in the past studies, whereby they do not consider the shock of the oil prices and gold prices. Hence, NARDL approach is employed in this paper to ascertain whether OVX and GVZ have asymmetric effects on the realized volatility of KLCI. The empirical results show that there is existence of asymmetric long run relationship among volatility of oil market, volatility of gold market and volatility of Malaysian stock market. Specifically, RV of KLCI tends to react more to OVX+ instead of OVX- which means that an increase in volatility of oil market will increase the volatility of Malaysian stock market. On the other hand, RV of KLCI tends to react more to GVZ- instead of GVZ. This implies that a decline in volatility of gold market will decrease the volatility of Malaysian stock market. The findings of this study carry important implications for investors, fund managers, government policymakers and researcher